SINTESIS DAN KARAKTERISASI NANOPARTIKEL OKSIDA BESI MENGGUNAKAN METODE BALL MILLING DAN KOPRESIPITASI - Riduan Alvinsen Sirait; Salomo Salomo; Juandi Muhammad; Erman Taer (Komunikasi Fisika Indonesia, 2022)
This Research has carried out on natural sand originating from the Rokan river, Riau Province by converting it into magnetic iron oxide nanoparticles to determine changes in magnetic properties and particle size. Natural sand samples of the Rokan river were separated between magnetic and non-magnetic particles using an iron sand separator (ISS). ISS products are further synthesized using ball milling and coprecipitation methods. 70-hour ball milling products, coprecipitation without ball milling and coprecipitation with 70-hour ball milling are then given NdFeB (neodymium iron boron) magnets to clean impurities containing non-magnetic elements. The results of this study showed that the highest magnetic acceptability value was obtained in coprecipitation products with ball milling, which was 12.9 × 10-2. This is because coprecipitation products have an abundant content of chemicals in the form of magnetic elements. Based on the results of chemical composition testing using X-ray flourescence (XRF) it was found that in coprecipitation products with ball milling there was 64.504% iron (Fe) content, while 70-hour ball milling products and coprecipitation without ball milling the percentage of Fe protection was 15.023% and 54.152%, respectively. Based on the results of the identification of the chemical composition in the sample, coprecipitation products with 70-hour ball milling have high magnetic induction values and magnetic suseptibility caused by the magnetic content in products such as Fe which are very high and non-magnetic content is very low such as Si compared to 70-hour ball milling products and coprecipitation products without ball milling.